SPECIAL EXERCISES COMPOSITE AND THEIR IMPACT ON THE DEVELOPMENT OF BALANCE AND THE SKILL OF THE INDIVIDUAL DEFENSIVE WALL BY JUMPING HIGH AMONG MISAN NAFT PLAYERS IN HANDBALL (Proximus Journal of Sports Science and Physical Education, 2025)
The objective of the study was to determine the influence of specialised compound exercises on the enhancement of balance and the ability of individual defensive wall players to jump higher in Naft Misan handball. The researcher employed an experimental approach that was suitable for the study's nature. The sample comprised 20 players from Anbar Sports Club, who were deliberately selected and divided into two groups: a control group and an experimental group, determined by lottery. Each group consisted of 10 players. The exploratory experiment was conducted, followed by the tribal tests, and finally the main experiment, which lasted for 8 weeks with 3 training units per week. The researcher considered the training level, age stage, and physical and skill abilities of the sample. The obtained results were processed using appropriate statistical methods. The researcher concluded that the special compound exercises applied to the research sample had a significant impact on the development of balance and defensive wall skill in high jump players of Naft Misan handball.